(untitled) (International Journal of Natural Sciences, 2016)
This study aimed to evaluate the efficacy of ivermectin, levamisole HCl and albendazole against gastrointestinal nematodes in naturally infected goats of government goat development farm, Sylhet, Bangladesh. The study included 52 black Bengal breed of which 30 were naturally infected and randomly selected 20 on the basis of their weight and egg count. Twenty black Bengal goats of 12-13 month old irrespective of sex infested with gastrointestinal nematodes were selected for this experiment and randomly divided into four equal groups (group A, B, C and D) where each group consisted of 5 goats and goats of group D were kept as control group. One injectable ivermectin (200?gkg-1 body weight, S/C) preparations (Techno Drugs Ltd. Bangladesh) and two solid levamisole HCl, albendazole (7.5 mgkg-1 body weight, orally) preparations (The ACME Laboratories Ltd. and Square Pharmaceuticals Ltd. Bangladesh) were used for positive control of gastrointestinal nematodes as group A, B and C. Goats of group D was kept as control without giving any treatment. Before trials (day 0), total egg count, blood samples and initial body weight were recorded. During the study period the fecal and blood samples were collected directly from rectum and examined on 7th, 14th, 21st and 28th day using McMaster fecal egg counting method. Body weight was recorded on day 28 following the treatments. The results of the comparative efficacies of different anthelmintic of ivermectin was 86.75%, followed by levamisole HCl 85.07% and albendazole 92.81%. McMaster fecal egg counting method discloses the percentage of Haemonchus spp. (15.38%), with Trichostrongylus spp, Strongyloides spp., and Cooperia spp. also present. After treatment with ivermectin, levamisole HCl and albendazole, Total Erythrocyte Count (TEC), Hemoglobin (Hb) content and Packed Cell Volume (PCV) were increased significantly (p<0.01 and p>0.05) in goats but Erythrocyte Sedimentation Rate (ESR) and Total Leukocyte Count (TLC) were decreased significantly (p<0.05 and p>0.01) in all treated goat and body weight was increased significantly (p<0.01) on day 28. International Journal of Natural Sciences (2015), 5(1) 26-34